A Sometimes Mercurial Process: New Protocols for the Preservation of Singapore’s Time Based Art Collection - Mar Cruz (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The conservation of Time Based Media (TBM) artwork deals in the world of bits, bytes, checksums and obsolescence, terms far different from the conservation of paper, paintings or sculpture. The processes behind the conservation of TBM artworks reflect the same esoteric nature. This case study seeks to show the advantages and challenges of creating a bespoke TBM-specific workflow by highlighting its efficacy in preempting a potentially large conservation issue in The Mercurial Inscription, an TBM installation artwork with software and interactive elements.